ANALISIS PENDAPATAN INDUSTRI RUMAH TANGGA KERIPIK DI KOTA TARAKAN - Oktaviani; Setiawan, Rusdy; Irawati HM; Hatta, Djuanda; Suryaningsih; Masniah, Andi (Ekonomi Pembangunan Fakultas Ekonomi, 2024)
This research aimed to determine the income of the household scale chips industry in Tarakan City. The data analysis technique uses business income analysis using a quantitative approach. The results of the business income analysis calculation show that the calculated income for Qobidh chips is IDR 44,183,200, Narlam chips IDR 31,881,000 Indri chips IDR 56,333,167 and 3 Dara chips IDR 61,401,500. Using business analysis calculations, namely B/C, the ratio of Qobidh chips is 1.58, Narlam chips 1.27, Indri chips 1.66, and 3 Dara chips 2.33. For the Break Event Point calculation, Qobidh chips are BEP unit 1,112.67/pouch and BEP price Rp9.658,61, Narlam chips are BEP unit 1.250,59/pouch and BEP price Rp.8.794,02, Indri chips are BEP unit I .356,67 /pouch and BEP price Rp9.395,24, and chips 3 Dara BEP unit 1,063.94/pouch and BEP price Rp7.556,39. The payback period calculation results for Qobidh chips are 3.83 years, Narlam chips 1.24 years, Indri chips 1.07 years, and 3 Dara chips 1.68 years